Managerial Gender Diversity and Firm Performance: An Integration of Different Theoretical Perspectives - Schwab, Andreas; Werbel, James D.; Hofmann, Heike; Henriques, Paulo L. (Group & organization management, 2016)
This study examines the relationship between managerial gender diversity (MGD) and firm performance. It outlines how extremely low and extremely high levels of MGD can trigger group processes that can impede the attainment of the performance benefits associated with moderate levels of MGD. Findings from longitudinal panel data from financial service firms in Portugal suggest that the effects of MGD on firm performance are best captured by a non-linear function with two breaking points. This study introduces a framework that combines different theoretical perspectives focused on tokenism, subgroup formation, divergent thinking, and other group processes linked to positive and negative gender-diversity consequences. Corresponding overall firm-performance outcomes are contingent upon the level of MGD.